Pan-Cancer Analysis of the Characteristics of LY96 in Prognosis and Immunotherapy Across Human Cancer - Nie, Kechao; Li, Jing; Peng, Luqi; Zhang, Mei; Huang, Wei (Frontiers in Molecular Biosciences, 2022)
Lymphocyte antigen 96 (LY96) was implicated in tumorigenesis by modulate host immunity. However, an integrated pan-cancer analysis of LY96 in prognosis and immunotherapy across human cancer is still lacking. Therefore, we analyzed the LY96 expression and its prognostic role in tumors by multiple databases. We also investigated the correlation between LY96 and copy number, DNA methylation, somatic mutation, microsatellite instability (MSI) and tumor mutation burden (TMB), tumor microenvironment (TME) and immune cells infiltration across human cancers. In addition, the biological processes related to LY96 across various tumors and correlation between LY96 and 50% inhibitive concentration (IC50) of various drugs was investigated. We found that LY96 was differently expressed between tumor and normal tissues and was significantly upregulated in most types of cancers. LY96 was gradually upregulated from stage I to IV in several cancers. Moreover, we found LY96 may act as prognostic role in most cancers and patients with high or low LY96 expression often showed different clinical outcome. LY96 was also associated with copy number, DNA methylation, somatic mutation, MSI, TMB, TME characteristics and immune cells infiltrates in cancers. LY96 may also regulated classic tumor-associated pathways in several cancers and was related to drug resistance. This article may help to elucidate the role of LY96 in tumorigenesis, which may promote the development of immunotherapy and targeted therapy in cancers.